Axisymmetric bend of the lithospheric plate of the exponential profile - A. A. Baimukhametov; A. A. Kultasov; P. B. Abdimanapova; Zh. B. Mazhit (Алматы технологиялық университетінің хабаршысы, 2021)
Earth 's seismic and volcanic activity is related to plate tectonics. Thin elastic surface plates form a lithosphere which experience different loads. The article considers a new model of the stressstrain state of the axisymmetric lithospheric plate of exponential profile in a non-uniform temperature field and under the influence of transverse forces. Novelty of solution of this problem lies in study by method of partial sampling of nonlinear differential equation with non-uniform coefficients when the lithospheric plate is bent. There are obtained regularities of change of radial force and bending moments under action of radial uniformly distributed load and volumetric centrifugal forces, as well as a result of temperature heating. A graphic analysis indicates the non-linear nature of their distribution, which significantly affects the shape of a curved plate.